2018
DOI: 10.1039/c8cp01922c
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-based amino-functionalized lipids for gene transfection: 3D phase behaviour and transfection performance

Abstract: Based on previous work, the influence of the chain composition on the physical-chemical properties of five new transfection lipids (TH10, TT10, OH10, OT10 and OO10) containing the same lysine-based head group has been investigated in aqueous dispersions. For this purpose, the chain composition has been gradually varied from saturated tetradecyl (T, C14:0) and hexadecyl (H, C16:0) chains to longer but unsaturated oleyl (O, C18:1) chains with double bonds in the cis configuration. In this work, the lipid dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…7 E) [ 48 ]. The presented cell adhesion studies underline the beneficial effect of Col I as the terminal surface layer but also that the adsorbed liposomes possess an excellent biocompatibility as found in our previous studies [ 27 , 28 ].…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…7 E) [ 48 ]. The presented cell adhesion studies underline the beneficial effect of Col I as the terminal surface layer but also that the adsorbed liposomes possess an excellent biocompatibility as found in our previous studies [ 27 , 28 ].…”
Section: Resultssupporting
confidence: 78%
“…The addition of cationic liposome, LbL sequence [CS, Col I] 4 -CS-Lip, results in a PZC at higher pH values (around pH 6) due to the primary amino functions in the head group. In a previous work the pKa of OO4 was determined at pH 6 [ 27 ], this means that more than 99% of the lipid species are uncharged at pH ≈ 8. The observed shift in the PZC also supports that liposomes were irreversibly adsorbed on the surface and do not desorbing during the washing steps with NaCl.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…50 Nevertheless, recently, we demonstrated that a lipoplex formulation with a lamellar superstructure was more efficient than a lipoplex with a cubic structure. 51 Obviously, more factors (for instance lipoplex stability, lipoplex charge, and binding strength between lipids and DNA) than the fusiogenic potential of cubic phases affect the transfection efficiency.…”
mentioning
confidence: 99%